PERANGKAT LUNAK KEAMANAN DATA MENGGUNAKAN ALGORITMA KRIPTOGRAFI SIMETRI TINY ENCRIPTION ALGORITHM (TEA) - Rohmat Nur Ibrahim (Jurnal Computech & Bisnis (e-Journal), 2019)
Data security is one of the most important aspects in information technology. With a high level of security, it is expected that the information presented can be maintained its authenticity. The method for forming systems uses object-oriented methods. By using the Tiny Encryption Algorithm (TEA) Algorithm which is a symmetric key cryptographic algorithm, this problem can be overcome. The strength of this algorithm lies in feistel networks (including substitution operations, permutations and arithmetic modular), the implementation of which is analyzed using the encryption and encryption message encryption process in text format (as in * .txt format). Data security software is expected to be achieved so that other researchers who will research further can develop it again.Keywords: Data Security, Algorithms, Symmetry, TEADOI : http://doi.org/10.5281/zenodo.3625286